2011
DOI: 10.1200/jco.2010.32.0598
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability-Adapted Imatinib 800 mg/d Versus 400 mg/d Versus 400 mg/d Plus Interferon-α in Newly Diagnosed Chronic Myeloid Leukemia

Abstract: Treatment of early-phase CML with imatinib can be optimized. Early high-dose therapy followed by rapid adaptation to good tolerability increases the rate of MMR at 12 months. Achievement of MMR by month 12 is directly associated with improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
240
4
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(262 citation statements)
references
References 38 publications
15
240
4
3
Order By: Relevance
“…Notably, although high‐dose imatinib has been associated with poor tolerability (Cortes et al , 2010; Hehlmann et al , 2011), most patients who had nilotinib dose escalation in this study were able to maintain the higher dose, with 83 of 88 remaining on nilotinib 400 mg twice daily at the end of treatment. Although some of these patients (14 of 88; 15·9%) later discontinued treatment due to suboptimal response or treatment failure, the majority (63·6%) achieved MMR by 24 months.…”
Section: Discussionmentioning
confidence: 72%
“…Notably, although high‐dose imatinib has been associated with poor tolerability (Cortes et al , 2010; Hehlmann et al , 2011), most patients who had nilotinib dose escalation in this study were able to maintain the higher dose, with 83 of 88 remaining on nilotinib 400 mg twice daily at the end of treatment. Although some of these patients (14 of 88; 15·9%) later discontinued treatment due to suboptimal response or treatment failure, the majority (63·6%) achieved MMR by 24 months.…”
Section: Discussionmentioning
confidence: 72%
“…Assignment to the study arms using imatinib in combination with cytarabine and imatinib after failure of IFN was terminated in 2005. 17 Cytogenetic and molecular analyses Cytogenetic response was determined by conventional metaphase analyses with standard G-banding or fluorescence R-banding techniques after shortterm culture. At least 20 bone marrow cell metaphases were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16] So far, results of the German CML Study IV showed a superior OS of patients achieving p1% BCR-ABL IS at 12 months of treatment, which was associated with a 3-year survival of 98% as compared with 93% in the 41% group. 17 The aim of the present study was to clarify the relation between early kinetics of molecular and cytogenetic response and the risk for disease progression and death in patients receiving imatinib treatment. Analyzing patients of the German CML Study IV, we report here molecular and cytogenetic milestones to be achieved at 3 and 6 months of treatment to ensure the most favorable outcome and effective TKI treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For patients in CCyR, the achievement and maintenance of a MMR is of debatable significance. Several studies evaluating patients receiving imatinib or second generation have found that patients in CCyR have similar survival whether there is achievement of MMR or not [22,40,41].…”
Section: Important Points For Monitoring and Determining Treatment Famentioning
confidence: 99%